2013
DOI: 10.1007/s11255-012-0374-y
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of microRNA-100 predicts an unfavorable prognosis in renal cell carcinoma

Abstract: Our data offer convincing evidence that miR-100 overexpression strongly associates with advanced tumor progression and unfavorable clinical outcome of patients with RCC. miR-100 expression may be a useful prognostic marker for this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 15 publications
0
27
0
3
Order By: Relevance
“…Cell Physiol Biochem 2015; 37:2143-2159 of miR-100 has been also found in small cell lung cancer (SCLC) [82], NSCLC [83,84], GC [7,9,85], HCC [86], pancreatic adenocarcinoma [87][88][89], renal cell carcinoma (RCC) [90], acute myeloid leukemia (AML) [91][92][93][94]. However, the expression levels of miR-100 in the same cancer type could be different, which is dependent on the tumor samples obtaining in cancer cell lines or in cancer tissues, as well as plasma.…”
Section: Table 1 Dysregulation Of Mir-100 In Different Human Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell Physiol Biochem 2015; 37:2143-2159 of miR-100 has been also found in small cell lung cancer (SCLC) [82], NSCLC [83,84], GC [7,9,85], HCC [86], pancreatic adenocarcinoma [87][88][89], renal cell carcinoma (RCC) [90], acute myeloid leukemia (AML) [91][92][93][94]. However, the expression levels of miR-100 in the same cancer type could be different, which is dependent on the tumor samples obtaining in cancer cell lines or in cancer tissues, as well as plasma.…”
Section: Table 1 Dysregulation Of Mir-100 In Different Human Cancersmentioning
confidence: 99%
“…In terms of SCLC, Xiao et al confirmed that the expression level of miR-100 was inversely correlated with the expression of its target gene HOXA1 and associated with the poor prognosis of SCLC patients [82]. Wang et al showed that overexpression of miR-100 in RCC tissues was associated with advanced tumor T stage, grade, the presence of metastasis and poor prognosis of patients [90]. Moreover, low expression of miR-100 was testified to be a negative prognostic factor, associating with gene signatures of high grade undifferentiated breast cancer [34].…”
Section: Mir-100 In Cancer Diagnosis and Prognosismentioning
confidence: 99%
“…In breast cancer, silencing of miR-100 initiated apoptosis [106] and the same effect was also observed in gastric tumour [107]. High miR-100 expression in renal carcinoma cells was associated with poorer prognosis [108], but not in hepatocellular carcinoma where downregulation of miR-100 was associated with poorer cell differentiation and shorter recurrence-free survival, while activation of miR-100 repressed metastasis [109]. In oesophageal squamous cell carcinoma [110], colorectal cancer [111], bladder carcinoma [112] and ovarian cancer [113] miR-100 downregulation was generally found to be associated with a poorer prognosis.…”
Section: Introductionmentioning
confidence: 97%
“…In addition to these, the downregulation of miR-100 was also shown in hepatocellular carcinoma, oral cancer, and adrenocortical cancer (Henson et al, 2009;Doghman et al, 2010;Chen et al, 2013). In contrast, an upregulation of miR-100 has been observed in renal cell carcinoma, acute myeloid leukemia, and prostate cancer (Akbari Moqadam et al, 2013;Wang et al, 2013;Wang et al, 2014). Previously, Oliveira et al (2011) found that miR-100 acted as a tumor suppressor in human bladder carcinoma 5637 cells.…”
Section: Discussionmentioning
confidence: 96%